Leptin Action in the Ventromedial Hypothalamic Nucleus Is Sufficient, But Not Necessary, to Normalize Diabetic Hyperglycemia - Meek, Thomas H. (Endocrine Society, 2013)
In rodent models of type 1 diabetes, leptin administration into brain ventricles normalizes blood glucose at doses that have no effect when given peripherally. The ventromedial nucleus of the hypothalamus (VMN) is a potential target for leptin's antidiabetic effects because leptin-sensitive neurons in this brain area are implicated in glucose homeostasis. To test this hypothesis, we injected leptin directly into the bilateral VMN of rats with streptozotocin-induced uncontrolled diabetes mellitus. This intervention completely normalized both hyperglycemia and the elevated rates of hepatic glucose production and plasma glucagon levels but had no effect on tissue glucose uptake in the skeletal muscle or brown adipose tissue as measured using tracer dilution techniques during a basal clamp. To determine whether VMN leptin signaling is required for leptin-mediated normalization of diabetic hyperglycemia, we studied mice in which the leptin receptor gene was deleted in VMN steroidogenic factor 1 neurons using cre-loxP technology. Our findings indicate leptin action within these neurons is not required for the correction of diabetic hyperglycemia by central leptin infusion. We conclude that leptin signaling in the VMN is sufficient to mediate leptin's antidiabetic action but may not be necessary for this effect. Leptin action within a distributed neuronal network may mediate its effects on glucose homeostasis.